PENGEMBANGAN DAN VALIDASI METODE ANALISIS UNTUK PENETAPAN KADAR SENYAWA ORGANIK DALAM PRODUK KOSMETIK PEWARNA KUKU SECARA KROMATOGRAFI GAS - Made Anggraeni, Marcellina
In nail polish cosmetic products, there are various organic compounds that act as solvents or excipients, including toluene and n-butanol. At certain levels of exposure, these organic compounds can cause harmful effects to the body. This study aims to validate methods of analysis using gas chromatography to determine the levels of toluene and n-butanol simultaneously at various nail polish cosmetic products. Nail polish samples were diluted with methanol to dissolve the analytes and then were analyzed by gas chromatography. This analysis used Flame Ionization Detector (HD), OV-1 capillary column 25 m x 0.53 mm and nitrogen as the carrier gas. Optimization method was obtained on condition of column temperature 38 °C for 5 min, with injector and detector temperature 270 °C. Correlation coefficient (r) of toluene and n-butanol were 0.999. Coefficient variancy (Vx0) were 0.69 and 1.69%. Limit of detection were 3.17 and 7.8 ppm. Limit of quantitation were 9.6 and 23.65 ppm. Accuracy revealed a percentage of recovery in a range of 99.47¬101.55% for toluene and 98.00-101.99% for n-butanol. Precision test revealed a coefficient of variance for toluene and n-butanol of 1.43 and 1.42% for the first day, 1.59 and 1.83% for the second day, and 1.26 and 0.58% for the third day. Level of toluene in sample A, B and C were 13.11%, 21.10% and 5.21% respectively. Level of n-butanol in sample A, B and C were 22,649.75 ppm, 4,001.23 ppm and 5,029.02 ppm respectively. The analytical method using gas chromatography could be used to determine the level of organic compounds in a variety of nail polish cosmetic products and can be used for quality analysis. Level of toluene in sample A, B and C meet BPOM requirements. Level of n-butanol in sample A, B, and C exceed the permissible exposure limit by OSHA.